Turner na literarni sceni in v njenem zakulisju - Grdina, Igor (Studia Historica Slovenica, 2001)
Pavel Turner (1842-1924) dealt with literature marginally. In spite of this, from his published texts and correspondence it is possible to grasp a sufficiently consistent literary programme. As an utilitarist as to worldview, he advanced the principle that every even with respect to literature - piece of writing must serve the education of the largest strata of the Slovene nation
Keywords: izobraženci; kulturna zgodovina; literarna zgodovina; slovenska inteligenca; slovenska književnost; Turner, Pavel